Fibrinogen: a possible link between social class and coronary heart disease. - Markowe, H L (1985)
Mortality from coronary heart disease in civil servants in the lowest grade of employment has been found to be about three times that of men in the highest grade of employment. As part of an investigation of this finding several haemostatic variables were measured in a sample of 29 men in lower grades of employment and 45 men in higher grades. There was a significant difference in plasma fibrinogen concentrations between men in lower grades of employment and those in higher grades (mean 3.39 g/l v 2.95 g/l, respectively; p less than 0.01) but not in other haemostatic variables. Multiple regression analyses showed significant independent associations of fibrinogen concentration with smoking (p less than 0.05) and grade of employment (p less than 0.05). The size of the observed difference between the grades of employment was similar to that between those dying of coronary heart disease or surviving during longitudinal study; it may therefore be an important part of the mechanism underlying social class differences in coronary heart disease. The statistical relation between fibrinogen concentrations and other characteristics that may be concerned in the aetiology of coronary heart disease was examined. A summary measure of job stress was significantly related to fibrinogen concentration (p less than 0.01) and made a substantial contribution to explaining the differences between grades of employment. Behaviour type and a score of physical activity were not significantly related to fibrinogen concentration.